Expression Levels of Activated Leukocyte Cell Adhesion Molecule (ALCAM/CD166) in Primary Breast Carcinoma and Distant Breast Cancer Metastases. Issue 2 (2nd June 2013) - Ihnen, M.; Köhler, N.; Kersten, J. F.; Milde-Langosch, K.; Beck, K.; Höller, S.; Müller, V.; Witzel, I.; Jänicke, F.; Kilic, E.
Abstract : Introduction: Activated Leukocyte Cell Adhesion Molecule (ALCAM/CD166) gained increasing attention regarding tumorprogression and metastatic spread in breast cancer. The aim of this study was to examine ALCAM expression levels in primary breast cancer and distant metastases of the same patient within 29 autopsy cases to better understand the underlying mechanisms of metastases and the role of adhesion molecules in this process. Material and Methods: Paraffin-embedded tissue of the primary and distant metastases (N = 84) were collected and ALCAM immunohistochemistry was performed. Results: The primary tumor and all metastases showed a statistically normally distributed ALCAM expression. ALCAM expression level average differs between immunoreactive score (IRS) (mean) 4.16 (lung)-5.00 (adrenal gland). Of the metastatic ALCAM expression levels we obtained an intra-class correlation (ICC) of 80.9%, indicating a strong cluster effect of measurements in the same patient. ALCAM expression scores in metastatic sites and in the primary analyzed by hierarchical regression analysis showed that ALCAM expression in the primary is prognostic for ALCAM expression in all different sites of metastases (slope = 0.773, p < 0.001, r 2 = 0.504). Conclusion: ALCAM expression in the primary is positively correlated to ALCAM expression in metastases within one single patient. This could show a tumorbiological context of ALCAM for the development of metastases in breast cancer.